Conversation difficulties rather than language deficits are linked to emotional problems in school children with hearing loss - Holzinger, Daniel; Fellinger, Johannes (Frontiers in Education, 2022)
Background: Social communication difficulties are often associated with neurodevelopmental disorders such as language disorder, intellectual development disorder, attention deficit hyperactivity disorder and autism spectrum disorder, which impedes the investigation of the specific role of social communication problems in mental health outcomes. Aims: We investigated the association between conversation difficulties and increased risk of mental health problems in schoolchildren with hearing loss. It can be assumed of this sample that conversation difficulties are primarily due to limited auditory access to language rather than neurobiological deficits. Methods: Five complete birth cohorts of Carinthian children (n=53) with significant hearing loss and an intelligence quotient over 70 were assessed in terms of language abilities in standardised tests and in terms of their conversation skills by use of a short teacher checklist developed by the authors. Mental health problems were assessed by means of the Strengths and Difficulties Questionnaire by parents and teachers. Results: Conversation skills were significantly correlated with lower SDQ emotional problems and total problem scores as rated by parents and lower peer problems scores as rated by teachers. Controlling for degree of hearing loss, maternal education and language skills, confirmed the specific value of conversation skills as a predictors of emotional problems (p=.010). Conclusion: With regard to mental health, our results suggest a focus on the assessment of conversation skills in addition to language abilities.